Farming Practices and Livelihood of the Coastal People of Bangladesh - Uddin, MT; Nasrin, M (Progressive Agriculture, 2014)
The present study was designed to assess the farming patterns and farmers livelihood in coastal regions of Bangladesh. Three coastal districts namely, Khulna, Satkhira and Bagerhat located in the southwest of Bangladesh were selected to conduct the study. Fifty shrimp farmers from each district (a total of 150 farmers) were selected for necessary data collection on the basis of farm size category (i.e., small, medium and large) following stratified random sampling technique. Descriptive statistics like sum, average, percentages, etc. were derived and calculated for analyzing the data. It was found that the farming system of coastal region was mainly shrimp based. The amount of land devoted to agricultural crop cultivation was declined due to shrimp cultivation for all categories of farmers. Number of livestock except poultry and duck was decreasing due to shortage of feed. Native fish species in fresh and open water bodies were also disappearing gradually. Lower crop production was observed through surveyed region due to lower productivity of land caused by salinity. However, shrimp cultivation opened up new avenues for employment for the local people especially for women. Small farmers get higher proportion of income (75.0% of total farm income) from shrimp farming than medium (67.4%) and large farmers (73.6%). On an average, farmers income was increased which enhanced overall socioeconomic condition and livelihood status. In spite of various adverse impacts of shrimp farming, it can be recommended that proper planning, regulation and motivation of the farmers are needed to develop an environment friendly shrimp farming as well as to maintain sustainable agricultural production practices in the coastal regions of Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19177 Progress. Agric. 24(1&2): 251 - 262, 2013